PENINGKATAN UNJUK KERJA HIDROLISIS ENZIMATIK JERAMI PADI MENGGUNAKAN CAMPURAN SELULASE KASAR DARI Trichoderma reesei DAN Aspergillus niger (Makara Journal of Science, 2010)
Increasing the Performance of Enzymatic Hydrolysis of Rice Straw Using Mixed Crude Cellulases from Trichoderma reesei and Aspergillus niger. The objective of this work is to compare the effectiveness of mixed crude enzyme cellulase from T. reesei and A. niger with commercial enzyme from A. niger, and to investigate effect of enzyme to substrate ratio to performance of enzymatic hydrolysis of rice straw. The commercial enzyme from Fluka Biochemica was used, and crude enzyme were prepared by solid fermentation with simple media. Before hydrolized, the rice straw was grinded and sieved and then heated at 85 o C with 2% sodium hydroxide for six hours. Hydrolysis was conducted in 300 mL beaker flask equipped with mechanical stirrer. Samples were analyzed by dinitrosalicylic acid method and measured by spectrophotometer. Both of commercial and mixed crude enzyme show that, the higher enzyme to substrate ratio was higher the glucose concentration obtained. However, ratio of glucose obtained to enzyme used become smaller. The mixture of crude enzyme from T. reesesi dan A. niger that produced in this work was two fold more effective to hydrolyze rice straw than using cellulase enzyme of A. niger from Fluka Biochemika